Honesty in Indonesian literature : its social and cultural factors - Dwijatmoko, Benedictus Bherman (Penerbit Universiti Kebangsaan Malaysia, 2018)
As an important life value, honesty is well reflected in Indonesian literature. It appears in a large number of talks and events, which involve the characters of many of its literary works. This paper is a report on a corpus study of the social and cultural factors that influence the characters' honesty as shown in the use of the words jujur (honest), sejujurnya or sejujurjujurnya (most honest), and kejujuran (honesty). The result reveals that social position, intimacy, life and work norms, and erotic capital may affect a person's view of honesty and its practice. A person with a high social position may influence a person with a lower social position to be honest or dishonest, and the person finds it difficult not to obey him. A person having an intimate relation with another person does not hesitate to talk about matters which may threaten the addressee's negative face or his own positive face. In real life and work place, honesty is required as a norm for a person to be fully accepted. A person with a big erotic capital may gain trust from other people more easily and be considered honest. The study also reveals that the words jujur (honest) and sejujurnya or sejujur-jujurnya (most honest) are often used as a hedge to avoid a negative face-threatening act to the addressee and maintain the speaker a positive face. The speaker requests the addressee's understanding that he is a position which requires him to say something the addressee does not like.